IMMISCIBLE PHASES OF MAGMATIC FLUID AND THEIR RELATION TO BE AND MO MINERALIZATION AT THE YERMAKOVKA F-BE DEPOSIT, TRANSBAIKALIA, RUSSIA - Reyf F.G. (My University, 2004)
Melt and fluid inclusions in minerals from the peralkaline granite intrusion and associated mineralized country rocks from the Yermakovka F–Be deposit were studied to characterize the behaviour of trace elements and exsolved fluids in the transition from magmatic to hydrothermal processes. Ore mineralization was mostly due to volatile release from a deep-seated pluton for which crystallization history and fluid exsolution can be tracked by three batches of magma (Gr1→Gr3) intruded at the level of the ore deposition to form the Yermakovka stock. Each batch of the sequential granite group is found to intrude at decreasing temperature (from 840 to 730 °C) and progressively increasing extent of crystallization of magma in the parental pluton. This resulted in the enrichment of the ascending melts in H2O (3.9 to 6.1 wt.%), F (2.6 to 4.1 wt.%) and some incompatible elements (Zr, Nb, Th, Rb, Pb). Although the earliest evidence for the exsolution of homogeneous fluoride–sulphate brine correlates with the final stage of the Gr2 ascent, the most intensive volatile(s) release from the emplaced magmas is shown to occur during their in situ crystallization, which was associated with the separation of exsolved fluid into immiscible phases, brine and low-salinity solution. Compositions of these fluid phases are determined using atomic emission spectroscopy of the appropriate fluid inclusions opened by a laser microprobe and EMPA and SEM–EDS analyses of daughter crystals. The brine phase is enriched in Mo, Mn, Be (up to 17, 8, and 0.3 g/kg, respectively) and contains perceptible abundances of Ce, La, Pb, Zn, whereas the low-salinity phase is enriched only in Be (up to 0.6 g/kg). The selective mobilization of the metals from the melt into fluids is considered to result from the oxidized state of the melt and fluids, peralkalinity of the melt during crystallization, and high F content of the melt. The immiscible fluid phases are shown to migrate together through the solidifying stock giving rise to the albitized granite that is enriched in molybdenite but devoid of Be minerals. In the country rocks, solutions similar to the brine and low-salinity phases of the magmatic fluid made up separate fluid flows, which produced Be and Mo mineralization and were issued predominantly from the parental pluton. Both types of mineralization are nearly monometallic which suggests that of the metals, jointly transported by the brine, only Mo and, in part, Ce and La precipitated separately at the level where the low-salinity solutions deposited Be ores.